2023
DOI: 10.1111/jnp.12339
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous unilateral spatial neglect recovery after brain tumour resection: A multimodal diffusion and rs‐fMRI case report

Abstract: Patients with unilateral spatial neglect (USN) are unable to explore or to report stimuli presented in the left personal and extra‐personal space. USN is usually caused by lesion of the right parietal lobe: nowadays, it is also clear the key role of structural connections (the second and the third branch of the right Superior Longitudinal Fasciculus, respectively, SLF II and III) and functional networks (Dorsal and Ventral Attention Network, respectively, DAN and VAN) in USN. In this multimodal case report, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Burkhardt et al (2023) showed that three French-speaking people with a left anterior tumour affecting the left inferior longitudinal fasciculus had difficulties retrieving the names of famous people, particularly after tumour removal surgery. Zigiotto et al (2023) presented a case of an Italian speaker with a right parietal tumour and left neglect that recovered after surgery. The authors stressed the importance of fronto-parietal networks relative to neglect.…”
Section: Introduction To the Special Issue On Cognitive Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Burkhardt et al (2023) showed that three French-speaking people with a left anterior tumour affecting the left inferior longitudinal fasciculus had difficulties retrieving the names of famous people, particularly after tumour removal surgery. Zigiotto et al (2023) presented a case of an Italian speaker with a right parietal tumour and left neglect that recovered after surgery. The authors stressed the importance of fronto-parietal networks relative to neglect.…”
Section: Introduction To the Special Issue On Cognitive Neurosurgerymentioning
confidence: 99%
“…Zigiotto et al. (2023) presented a case of an Italian speaker with a right parietal tumour and left neglect that recovered after surgery. The authors stressed the importance of fronto‐parietal networks relative to neglect.…”
mentioning
confidence: 99%